Executive Director's Message - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2015)
This past year has been full of changes, adjustments, and taking stock of where ORNAC is as an organization. A strategic planning process in November 2014 included participation by the ORNAC Board of Directors, the ORNAC National Exhibitors Advisory Committee (NEAC), the Canadian Patient Safety Institute (CPSI), a patient representative of Patients for Canadian Patient Safety, and an ORNAC member at large. Input was also provided by the Canadian Medical Association (CMA), the Canadian Nurses Association (CNA) in the area of certification for Perioperative Registered Nurses, contact has recently been made with the Canadian Anaesthesiologist Society (CAS). With this input from key stakeholders we have set the direction of ORNAC over the next three years.